Pengaruh Media Sosial, Body Image dan Pola Makan pada Remaja Penari Bukittinggi: Pengaruh Media Sosial, Body Image dan Pola Makan pada Remaja Penari Bukittinggi - Faiz Nur Hanum; Fathia Maulida (Universitas Airlangga, 2023)
Background: Changes in growth and development in adolescents make their health problems need special attention, which will affect nutritional status through changes in diet and lifestyle. Factors that influence adolescents' eating patterns are perceptions of body image, social media and environmental factors, and nutritional status changes. Poor consumption patterns will affect the intake of nutrients consumed by adolescents, as well as being more vulnerable to chronic diseases in adulthood. Objectives: This research aimed to determine the relationship between the use of social media, body image, and eating patterns among young dancers in the city of Bukittinggi. Methods: The quantitative method with a cross-sectional survey design approach. The population of this study was adolescents aged 14-17 years who took part in traditional dance studios in the City of Bukittinggi between January and March 2022. A sample of 47 respondents was obtained by collecting data using a questionnaire. Results: Most respondents did not know about body image (66%). Most respondents already have a good diet with a frequency of ≥3 times a day (93.6%) and consume various foods. There is no relationship between social media exposure and diet, body image, eating patterns, the frequency of adolescents’ eating patterns, and nutritional status with a p-value > 0.05. Conclusions: Teenagers, especially young dancers, must increase awareness about body image and eating patterns and be educated about how they learn and see social media.